2023
DOI: 10.1109/jstars.2023.3250461
|View full text |Cite
|
Sign up to set email alerts
|

CroFuseNet: A Semantic Segmentation Network for Urban Impervious Surface Extraction Based on Cross Fusion of Optical and SAR Images

Abstract: The fusion of optical and synthetic aperture radar (SAR) images is a promising method to extract urban impervious surface (IS) accurately. Previous studies have shown that the feature-level fusion of optical and SAR images can significantly improve IS extraction. However, they generally use simple layer stacking for features fusion, ignoring the interaction between optical and SAR images. Besides, most of the features they used are shallow features manually extracted, such as texture and geometric features, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This result was similar to the accuracies found in our study; however, their F1-scores were higher than those in this study. Other recent studies have leveraged time series of SAR and multispectral imagery for impervious surface extent mapping with accuracies above 94%, often with various deep learning models [82][83][84][85]. One of the mentioned studies found SAR typically enhances overall accuracy by about 2%.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to the accuracies found in our study; however, their F1-scores were higher than those in this study. Other recent studies have leveraged time series of SAR and multispectral imagery for impervious surface extent mapping with accuracies above 94%, often with various deep learning models [82][83][84][85]. One of the mentioned studies found SAR typically enhances overall accuracy by about 2%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, synthetic aperture radar (SAR) photographs provide a rich array of landscape information from diverse material and physical viewpoints. SAR, an active sensor, detects backscatter information and is particularly sensitive to geometric features, such as surface roughness, temperature, and complex dielectric constants [3]. Although SAR images can penetrate obstacles and are impervious to water, they present challenges such as shortening, shadows, and speckle noise, making their imaging characteristics less intuitive for human visual interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…In many previous studies on urban impervious surfaces, multispectral data and SAR data have been fused together to extract urban targets, achieving improved classification results. However, previous research has mainly focused on the fusion of single optical data and SAR data, such as the fusion of Sentinel-2 MSI data with Sentinel-1 SAR data for impervious surface extraction [44,45], and the fusion of Landsat data with Sentinel-1 SAR data for impervious surface extraction [46]. Few studies have used multispectral data.…”
Section: Introductionmentioning
confidence: 99%